Concise Review: Human Induced Pluripotent Stem Cell Models of Retinitis Pigmentosa - Artero Castro, Ana; Lukovic, Dunja; Jendelova, Pavla; Erceg, Slaven (Stem cells (Dayton, Ohio), 2018)
Hereditary retinal dystrophies, specifically retinitis pigmentosa (RP) are clinically and genetically heterogeneous diseases affecting primarily retinal cells and retinal pigment epithelial cells with blindness as a final outcome. Understanding the pathogenicity behind these diseases has been largely precluded by the unavailability of affected tissue from patients, large genetic heterogeneity and animal models that do not faithfully represent some human diseases. A landmark discovery of human induced pluripotent stem cells (hiPSCs) permitted the derivation of patient-specific cells. These cells have unlimited self-renewing capacity and the ability to differentiate into RP-affected cell types, allowing the studies of disease mechanism, drug discovery, and cell replacement therapies, both as individual cell types and organoid cultures. Together with precise genome editing, the patient specific hiPSC technology offers novel strategies for targeting the pathogenic mutations and design therapies toward retinal dystrophies. This study summarizes current hiPSC-based RP models and highlights key achievements and challenges of these cellular models, as well as questions that still remain unanswered. Stem Cells 2018;36:474-481.
Keywords: genom lidský; transplantace kmenových buněk; Cell Differentiation; Gene targeting; editace genu; Retinal photoreceptors; Disease Models, Animal; Retinitis Pigmentosa; indukované pluripotentní kmenové buňky; Gene Editing; Genome, Human; Retina; Induced pluripotent stem; modely nemocí na zvířatech; zvířata; Humans; Autografts; Stem Cell Transplantation; Induced Pluripotent Stem Cells; Differentiation; buněčná diferenciace; Induced pluripotent stem cells; autologní štěp; retinopathia pigmentosa; Retinal pigmented epithelium; lidé; Animals